Analysis of caesarean section using Robson ten group classification system at Madhesh Institute of Health Sciences - Mahato, Raj Deb; Karki, Swekchha; Issar, Chandra Rekha; Subedi, Shanti (Medical Journal of Eastern Nepal, 2025)
BackgroundCaesarean section (CS) is one of the most commonly performed and lifesaving surgical procedures in modern obstetrics. The World Health Organization (WHO) recommends the Robson Ten Group Classification System (TGCS) as a global standard for evaluating, monitoring, and comparing CS rates across healthcare institutions. This study was conducted to assess the rate of caesarean deliveries and to analyze their distribution using the Robson classification system at the Madhesh Institute of Health Sciences (MIHS), Janakpurdham, Nepal.MethodsThis hospital-based, descriptive cross-sectional study was conducted in the Department of Obstetrics and Gynecology at MIHS. All women who underwent caesarean deliveries between February 17, 2024, and February 16, 2025, were classified into Robson groups. The study calculated the relative size of each group, its contribution to the overall CS rate, and the CS rate within each group.ResultsOut of 7,059 total deliveries, the overall caesarean section rate was 22.70%. Robson Group 5 (31.1%) multiparous women with at least one previous CS, a singleton pregnancy, and a cephalic presentation at term was the highest contributor to the overall CS rate. This was followed by Group 1 (22.5%) nulliparous women with singleton, term, cephalic pregnancies in spontaneous labor.ConclusionWomen with a previous caesarean section (Robson Group 5) represent the largest contributor to the overall CS rate. Promoting trial of labor after one previous caesarean and reducing primary caesarean deliveries may help in lowering the overall caesarean section rate.